Encyclopedia of food grains - Wrigley, Colin W.; Corke, Harold; Seetharaman, Koushik; Faubion, Jonathan; ScienceDirect eBooks (Kidlington, Oxford, UK : Academic Press is an imprint of Elsevier, 2016)
The Encyclopedia of Food Grains is an in-depth and authoritative reference covering all areas of grain science. Coverage includes everything from the genetics of grains to the commercial, economic and social aspects of this important food source. Also covered are the biology and chemistry of grains, the applied aspects of grain production and the processing of grains into various food and beverage products. With the paramount role of cereals as a global food source, this Encyclopedia is sure to become the standard reference work in the field of science.
Volume 1. The world of food grains -- volume 2.Nutrition and food grains -- volume 3. Grain-based procducts and their processing -- volume 4.The production and genetics of food grains.
Online resource; title from title details screen (ScienceDirect, viewed February 17, 2016).
Elsevier
Keywords: Grain -- Encyclopedias; Grain; TECHNOLOGY & ENGINEERING / Agriculture / Agronomy / Crop Science; Electronic books